Pengaruh Promosi Cashback Shopee Terhadap Perilaku Konsumtif - Adyanur Kholishoh, Siti; Ardani Putra, Ferdian (Medio Jurnal Ilmu Komunikasi, 2024)
One of the conveniences that we get in modern times is the ease in the process of selling and buying which is known as online shopping. Lately, in the online shopping process, there is a word that is popular with producers and consumers, namely cashback. Cashback is the prima donna in the world of online buying and selling, producers use this word to increase the number of sales and consumers use this word to get as much profit as possible. Consumptive behavior is consumption behavior that goes beyond the limit without being based on interests, by prioritizing ambition at all times. Referring to the background that has been explained earlier, the formulation of the problem is whether there is an influence of shopee cashback promotions on consumptive behavior?. This study aims to test the Effect of Shopee Cashback Promotion on consumptive behavior. In proving and analyzing the data, the Validity Test, Reliability, Classical Assumption Test, Simple Linear Regression Test and T Test were used. This data can be seen in the results of the hypothesis test which produced a calculated t value smaller than the t table -0.166 < 2,000 and a significant value was found to be 0.869 > 0.05, which means that ho is accepted and Ha is rejected.